Identifying the Effects of Sanctions on the Iranian Economy Using Newspaper Coverage - Dario Laudati; M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper considers how sanctions affected the Iranian economy using a novel measure of sanctions intensity based on daily newspaper coverage. It finds sanctions to have significant effects on exchange rates, inflation, and output growth, with the Iranian rial over-reacting to sanctions, followed up with a rise in inflation and a fall in output. In absence of sanctions, Iran's average annual growth could have been around 4 - 5 per cent, as compared to the 3 per cent realized. Sanctions are also found to have adverse effects on employment, labor force participation, secondary and high-school education, with such effects amplified for females.
Keywords: E31; E65; F43; F51; F53; O11; O19; O53; 330; newspaper coverage; identification of direct and indirect effects of sanctions; Iran output growth; exchange rate depreciation and inflation; labor force participation and employment; secondary education; and gender bias